Generating Requirement Dependency Graph Based on Class Dependency - Samosir, Hernawati; Siahaan, Daniel (IPTEK The Journal for Technology and Science, 2018)
A set of software requirements is an important element in software development. Engineers realize that requirements are interrelated. The interconnections between requirements indicate interdependences between requirements. This interdependence is crucial in decision-making processes of requirement engineering, such as a change management requirement, a version launch plan, and a requirement management. Researchers have been focused on visualizing dependency between requirements, analyzing the impact of changes in software by using changes to UML class diagrams, and predicting bug occurrences based on dependencies between requirements. Previous studies assumed that the requirements dependency information was pre-build by requirements engineer during the previous development process. This paper introduces a method that builds a requirements dependency model. The model was built based on realization associations between requirements and classes in the system design as well as dependencies between classes. The modeling process used semantic similarities between the requirements and the classes. A class is said to have a realization association with a requirement if and only if the semantic similarity is higher than a certain threshold. The output obtained from the dependent software development method was compared with the output produced by annotators. The method reliability was measured by the level of agreement between the method and the annotator using kappa statistical index. The preliminary result shows that the method was fair agreement (0.37) reliable as an annotator when generating requirements dependency graph.